Karakter Pendidikan Pada Masa Peradaban Islam di Luar Indonesia - Kusmawati, Heny; Kasanah, Nela Rofa’atul; Fasanah, Siti Nur (PT Literasi Nusantara Publisher, 2023)
The periodization of Islamic harmony is marked by the pubic era, decline and renewal. The existence of renewal in Islam also influences the characteristics and thinking of education. One of them is the Middle East as a model of renewal from the time of Islamic civilization. Educational reform was also influenced by several figures who spread Islam during the civilization at that time. Educational renewal in the Middle East, one of which is in Egypt, begins with the arrival of Napoleo Bonaparte. The existence of the Napoleon Bonaparte expedition brought changes in various fields, one of which was in the field of education, namely the establishment of scientific institutions. Apart from Napoleon Bonaparte, there were also Muhammad Rasyid Ridha and Sultan Mahmud II who were also influential in reforming education during the period of Islamic civilization in the Middle East.